Notes on feline internal medicine - Sturgess, Kit (Notes on, 2013)
"A unique text providing a quick, accessible, comprehensive, practical guide to help clinicians get started with a problem-solving approach to a sick cat. Published as part of the 'Notes on' series, it is written in an accessible note-based style, giving readers quick access to the most recent clinical and diagnostic guidance. This new edition includes new sections on sedation and anaesthesia, health screening, oncology, algorithms for critical care and practical tips on diagnostic techniques. The focus is on common conditions, and the second edition has been improved to avoid repetition of information"--Provided by publisher.